Single-Cell Dynamic Analysis of Mitosis in Haploid Embryonic Stem Cells Shows the Prolonged Metaphase and Its Association with Self-diploidization - Ao Guo; Shichao Huang; Jiali Yu; Huihan Wang; Haisen Li; Gang Pei; Li Shen (Stem Cell Reports, 2017)
The recent establishment of mammalian haploid embryonic stem cells (ESCs) provides new possibilities for genetic screening and for understanding genome evolution and function. However, the dynamics of mitosis in haploid ESCs is still unclear. Here, we report that the duration of mitosis in haploid ESCs, especially the metaphase, is significantly longer than that in diploid ESCs. Delaying mitosis by chemicals increased self-diploidization of haploid ESCs, while shortening mitosis stabilized haploid ESCs. Taken together, our study suggests that the delayed mitosis of haploid ESCs is associated with self-diploidization.